The Relationship Between Stock Return and Macroeconomic Factors: evidence from UK - Liu, Yuxin (2012)
This dissertation has explored the relationship between stock return and macroeconomic factors, in terms of interest rate, inflation, exchange rate, money supply and real economic activity. The econometric models are Granger Causality test and Vector Autoregression. We find the relationship between stock return and these macroeconomic variables suffers a cross effect, which therefore results some insignificant correlations, some of which are consistent with previous literature findings. We also find that the real economic activity is strongly correlated with stock return, as it is regarded as the underlying fundamental of national economy. Given we assume the market is efficient enough; the historical information might be useless to predict the future movements of stock market, which is another reason causes the insignificant relationships.